Improving the outcomes from electroactive constructed wetlands by mixing wastewaters from different beverage-processing industries. (November 2021) - Xu, Fei; Sun, Ruipeng; Wang, Hao; Wang, Yuting; Liu, Yongming; Jin, Xing; Zhao, Zheng; Zhang, Yujia; Cai, Wenjun; Wang, Chunxiao; Kong, Qiang
Abstract: Denitrification in electroactive constructed wetland (EW) systems is constrained by the carbon source and the carbon/nitrogen (C/N) ratio (the COD/TN ratio). In this study, wastewater with a high C/N from a brewery was added to wastewater with a low C/N (dairy wastewater) in an EW system, and the pollutant removal, bioelectricity generation, transformations of dissolved organic matter, and microbial community structures were evaluated. The results showed that the average removal rates of ammonium nitrogen, total nitrogen, and chemical oxygen demand from the wastewater mixture were 6.40%, 46.44%, and 23.85% higher than those from the wastewater with a low C/N, respectively. Dissimilatory nitrate reduction to ammonium was effectively inhibited, and the NH4 + -N removal was 25.52% higher, when the wastewater mixture was used instead of the high C/N wastewater. Similarly, the output voltage was significantly increased, and the internal resistance of the device was reduced, for the wastewater mixture. The structure of the microbial community improved, the relative abundance of electrochemically active bacteria was higher, and the protein-like and humic-like components were lower, in the mixture treatment than in the individual treatment. The results show that the nitrogen removal and biopower generation improved in an EW system when high C/N wastewater was used as the carbon source. Graphical abstract: Image 1 Highlights: The treatment efficiency of an EW improved by mixing different wastewaters. The NH4 + -N removal was increased 6.4%–25.52% in the mixed treatment. The mixed wastewater treatment had more EAB than the individual treatment. Improvement of DOM breakdown in mixed treatment due to increased microbial activity. The C/N and microbial communities influenced the pollutant removal in the EW.